Some want to change the world and others want to read it - Sequeira, Marta (International Seminar. Contemporary Architecture and Research - Universidade Autónoma de Lisboa, Centro Cultural de Belém, 2021)
«You cannot write about active architects. In this case, only the authors themselves have the right to write about their own work. Or rather: whatever they write is, well read, a comment about their own work – whether they recite us a state of measurements, invent a recurring dream of their childhood summer or shut up». This is what Josep Quetglas wrote in an article published in 2004 in Artículos de Ocasión. Although this passage is removed from its context, since it is, above all, part of an interesting consideration on architectural criticism – or at least that which proliferates by bad architecture journals –, it unveils a common place about the impossibility of seriously referring to contemporary production. Umberto Eco, in 1977, in the classic How to Write a Thesis, manifesting a solid experience – exposed in a didactic and, above all, very down-to-earth way, in the chapter entitled “Ancient or contemporary?” –, peremptorily states that “the contemporary author is always more difficult”, therefore implicitly recommending, for practical reasons, to choose, whenever possible, ancient authors as an object of study, over contemporary ones. In fact, it is common to say that doctoral theses on living authors should not be done; that about their work, it would be better for them to speak; that from them, there is no historical distance. However, the truth is that many research about the present or about a very recent past, as well as, in particular, about living authors, proved to be extremely fruitful.